Science E-Module for Improving Cultural Literacy among Fifth-Grade Elementary School Students - Figi Ardiyatama; Anwar Senen; Hammed Saheed Opeyemi (Universitas Muhammadiyah Surakarta, 2026)
Cultural literacy is an essential competency for elementary school students to understand and appreciate local cultural values within the learning process. However, its integration into science learning remains limited due to the lack of innovative and context-based instructional materials. This study aimed to develop and evaluate a science e-module titled Daerahku Kebanggaanku to enhance the cultural literacy skills of fifth-grade elementary school students. The study involved elementary school teachers and students in Kulon Progo, Yogyakarta. The research employed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The product was tested through individual, small group, and field trials, followed by implementation in experimental and control classes. Data were collected through interviews, observations, questionnaires, and tests, and analyzed qualitatively and quantitatively. The results indicate that the e-module is valid, practical, and effective in improving students’ cultural literacy, as evidenced by very feasible validation results and very practical teacher and student responses, with an N-gain score of 0.69 in the moderate category, indicating strong feasibility and greater student engagement and understanding in the Science and Social Science (IPAS) subject. These findings highlight the novelty of a culturally integrated e-module that supports meaningful science learning in elementary education.